Pengolahan Sampah untuk Mengurangi Sampah di Kelurahan Pamulang Barat, Kecamatan Pamulang, Kota Tangerang Selatan - Anggraeni, Retno; Sucahyanto (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2022)
This study aims to describe, analyze the management system, waste sorting carried out at TPS3R in reducing the burden of processing waste at the TPA by reducing waste generation from the source. This research was conducted from December 2021 to January 2022. This research method used a descriptive qualitative approach. The key informants in this research are the chairman, secretary, and waste collector of TPS3R Flamboyan; While the supporting informants are residents of RW 020 as members of the waste bank or the owner of the house served by the waste bank. Data collection techniques in this study use interviews (interviews) and documentation. The results of this study indicate that the purpose of the establishment of the Waste Bank and Waste Management Sites Reduce, Reuse, and Recycle TPS3R program is to reduce the burden of processing waste at the TPA by reducing waste generation from the source, in fact, it has not run optimally. Many waste banks and TPS3R only serve as locations for accumulation or only as a place for waste transit, only to be disposed of in the TPA, there is no processing or sorting of waste. Every day the largest contributor to waste is organic waste, namely food waste which is then processed into compost and several other commodities from processed waste. Ksm Flamboyan has two units of motorized vehicles for transporting garbage, starting at 08:00-10:00, the officers take the garbage from house to house after the garbage is taken it will be sorted at TPS3R Flamboyan. The compost will be distributed to the community for plant fertilizers and the waste material will be resold to collectors.